ABOUT PORTLAND CEMENT CLINKER MANUFACTURING PROCESS - Jovliyev Ziyodulla Anvar Ogli (American Journals, 2023)
A summary of research on process studies in the manufacture of Portland cement clinker.
Keywords: Portland cement, kilinker, wet method, dry method.